Artificial intelligence is revolutionizing everyday medical practice - Anna Rudnik; Oliver Jendro; Aleksandra Mastej; Natalia Gołuchowska; Piotr Rzepniewski; Tymon Zatorski; Artur Nowak (Kazimierz Wielki University, 2023)
Introduction This article discusses the impact of artificial intelligence (AI) on the medical field and its daily use in the practice of medicine. AI has applications in many stages of patient care, i.e.: prevention, diagnosis, personalising treatment plans, predicting disease progression and therapeutic outcomes or analysing medical images. GPs play a key role in patient care, but due to the complexity of medicine and the variety of symptoms, care and diagnosis can be time-consuming and difficult. Methods and materials The aim of this study is to explore and evaluate the potential of artificial intelligence in the process of diagnosing diseases by physicians and to provide practical suggestions and insights for its use in medical practice to improve the quality of healthcare. The methodology was based on material from PubMed and a review of the scientific literature on previous research and developments in AI in medicine.   State of knowledge Investment in artificial intelligence (AI) in medicine is growing rapidly. The role of GPs in patient care is highlighted and examples of the use of AI in everyday medical practice are given, including the role of Chatbots and the use of AI in specialised treatment.  Conclusions The conclusions of the article highlight the potential of AI in the area of physician-diagnosed diseases to reduce diagnosis time, increase accuracy of diagnoses and improve healthcare efficiency. Final diagnosis and therapy should still be determined by a qualified physician. There are areas where the doctor cannot be replaced by AI. AI cannot replace a doctor's diagnostic intelligence, empathy and rapport therefore doctors need to find a balance between these combinations to achieve better health outcomes with the highest possible care for patients.